Lembaga Negara Yang Mengatur Hukum Keluarga Dan Berfungsi Sebagai Penyelesaian Sengketa Hukum Keluarga (Peradilan Agama) - Sanusi, Muhammad Fahmi; Mustakim, Rizki; Sukendar, Rita; Kumbara, Ruhiyat; Abdillah, Tresna Mugni; Saepullah, Usep; Jamarudin, Ade (UIN Fatmawati Sukarno Bengkulu, 2024)
Abstract : state institution that has the authority to regulate family law as well as function as an institution for settling family law disputes in Indonesia, namely the Religious Courts, this is based on Pancasila and the 1945 Constitution of the Republic of Indonesia which is one of the executors and administrators of judicial power that has an equal position with other courts, then confirmed by the presence of Law No. 14 of 1970 concerning judicial power which was later added and amended by Law N0. 35 of 1999 was later amended by Law no. 48 of 2009 and in its implementation the Religious Courts are under the auspices of the Supreme Court as the Highest Court, of course with the existence of an equalization of the Religious Courts with other courts it gives authority to the Religious Courts to resolve and adjudicate cases under its authority independently. Law No. 7 of 1989 concerning the Religious Courts has explained what is the authority of the Religious Courts to resolve them.Keyword: Religious Courts, disputes and family law Abstrak : Suatu lembaga negara yang memiliki wewenang dalam mengatur hukum keluarga sekaligus berfungsi sebagai lembaga penyelesaian sengketa hukum keluarga di Indonesia yaitu Peradilan Agama, hal ini berdasarkan Pancasila dan Undan-undang Dasar Negara Republik Indonesia 1945 yang merupakan salah satu pelaksama dan penyelenggara kekuasaan kehakiman yang mempunyai kedudukan sejajar dengan peradilan-peradilan lainnya, kemudian dipertegas dengan hadirnya UU No.14 Tahun 1970 tentang kekuasaan kehakiman yang kemudian ditambah dan diubah dengan UU N0. 35 Tahun 1999 kemudian diubah dengan UU No. 48 Tahun 2009 dan dalam pelaksanaannya Peradilan Agama berada di bawah naungan Mahkamah Agung sebagai Pengadilan Tertinggi, tentu dengan adanya penyetaraan Peradilan Agama dengan peradilan lainnya memberikan kewenangan bagi Peradilan Agama untuk menyelesaikan dan mengadili perkara yang menjadi kewenangannya secara mandiri. Undang-undang No. 7 Tahun 1989 tentang Peradilan Agama telah menjelaskan apa saja yang menjadi kewenangan Peradilan Agama untuk menyelesaikannya.Kata kunci: Peradilan Agama, sengketa dan hukum keluarga